The Body as a Tool for Demanding Climate Action and Justice - Margaret Tilk; Antje Jacobs; Karin Hannes (Social Inclusion)
The escalating frequency and intensity of natural disasters underscore the urgency of the climate crisis. Against this backdrop, the global climate movement has surged, amplifying awareness of the climate emergency and pressuring governments and corporations to take decisive climate action. In climate manifestations, activists are increasingly using their entire body for/in climate activism, with Extinction Rebellion activists barricading driveways, and Just Stop Oil and Greenpeace activists gluing or tying their bodies to objects. These bodily ways of participating in climate activism have provoked public and political hostility, with concerns being raised about these so‐called “radical” forms of bodily activism. In response to these growing hostilities towards bodily climate activism, this study maps how the body is intimately connected to other actors when performing activism. We conducted interviews with nine European climate activists and, based on their stories, we mapped themes of relational practice of bodily activism. Our findings suggest that the body as a tool for climate activism manifestations is in relation to other material agencies, including (a) the public space, (b) other climate activists, (c) material objects, (d) law enforcement, (e) the general public and media, and (f) climate governance and policy. The body is not a stable and autonomous figure, but a dynamic and ever‐changing political tool through its socio‐spatial configurations that co‐constitute climate activism, making the role of the individual body in climate change activism manifestations elusive. Through its relational transformative collectivity, bodily climate activism proves itself as a valuable form of non‐violent participation in politics.